Diurnal photosynthetic performance of two oak species from two provenances in a Mediterranean and a central European common garden - Holland, V; Reininger, N; Bantis, F; Brüggemann, W; Radoglou, K; Fotelli, M N (Photosynthetica, 2022)
Oaks may contribute to the stabilization of European forests under climate change. We utilized two common gardens established in contrasting growth regimes, in Greece (Olympiada) and Germany (Schwanheim), to compare the diurnal photosynthetic performance of a Greek and an Italian provenance of two Mediterranean oaks (Quercus pubescens and Q. frainetto) during the 2019 growing season. Although the higher radiation in the southern common garden led to a strong midday depression of chlorophyll a fluorescence parameters (maximum quantum efficiency of PSII, performance index on absorption basis), comparable light-saturated net photosynthetic rates were achieved in both study areas. Moreover, both species and provenances exhibited analogous responses. Q. pubescens had enhanced chlorophyll a fluorescence traits but similar photosynthetic rates compared to Q. frainetto, whereas the provenances did not differ. These findings indicate the high photosynthetic efficiency of both oaks under the current climate in Central Europe and their suitability for assisted migration schemes.
Keywords: gas exchange; Quercus frainetto; chlorophyll fluorescence; Quercus pubescens; diurnal variation; assisted migration